Factors Affecting Key Success of Community-Based Tourism Management in Chumphon Province, Thailand - Athip Jansuri; Chanyaphak Lalaeng; Mallika Subongkod; Nannaphat Suwannarat (Procedia Computer Science, 2025)
The success of community-based tourism management arises from both internal and external motivations of individuals, as well as community participation in every stage from the initial process. Additionally, the community must be prepared in terms of natural resources, culture, human capital, and other resources. The integration of cooperation among government agencies, the private sector, and the community is also essential to support tourism management. This study aimed to: 1) investigate the level of opinions regarding motivation, community participation, and the success of community-based tourism management in Chumphon Province, 2) examine the motivational factors affecting the success of community-based tourism management in Chumphon Province, and 3) study the community participation factors affecting the success of community-based tourism management in Chumphon Province. The sample consisted of 400 individuals involved in community-based tourism management in Chumphon Province. A questionnaire was used as the data collection tool. The statistical methods used for data analysis included frequency, percentage, mean, standard deviation, and hypothesis testing through multiple regression analysis. The results of the study showed that: 1) the overall level of opinions regarding motivation, community participation, and the success of community-based tourism management had a high average level, 2) motivational factors significantly affected the success of community-based tourism management at a 0.05 significance level, and 3) community participation factors significantly affected the success of community-based tourism management at a 0.05 significance level.
Keywords: Diverse Aspects of Tourism Research; Cruise Tourism Development and Management; Hospitality and Tourism Education